Development Strategy for Child-Friendly Cities In Ponorogo Regency the Perspective of Muhammad Umer Chapra - Rokamah, Ridho; Roihanah, Rif’ah; Mun’im, Abdul; Wongtanee, Chokchai (El-Barka Journal of Islamic Economics and Business, 2022)
Introduction/main objective: study this review existing strategies applied in the development of Child-Friendly Cities or Kota Layak Anak (KLA) in the Regency Ponorogo with Muhammad Umer's approach Chapra. Background Problems:Construction of KLA in Ponorogo Regency still has not yet can be embodied because six KLA stages have yet to be implemented in a manner whole a manner maximum. Realization of KLA in the District Ponorogo Becomes interesting research with M. Umer's perspective Chapra because as a figure economist Muslim he has to criticize theory economy conventional (which is also implemented in Ponorogo ), but he is not anti-starch with the theory. Novelty: with the study implementation of KLA in the District Ponorogo through M. Umer's perspective Chapra expected there is a new strategic solution that combines existing development _ conducted with applying the 5 principles of development and 3 principles of the life of M. Umer Chapra. Research Methods: Types study this is a study field with a qualitative approach, while Engineering data collection includes an interview, observation, and documentation. Finding/Results: Based on the results of research already _ carried out, the application of KLA in the District Ponorogo is not yet can be held in a manner maximum because exists various constraints. Conclusion: strategy of the government in realizing the development of KLA uses two approaches, namely top-down and bottom-up. The cause of the KLA not being able to materialize is due to the heavy tractability of the problems, the ability of statute to structure implementation, and variables nonstatutory variables affecting implementation beneficiaries of this program do not yet have a big commitment in realizing this program. Those problems no will appear if in implementation government added five principles of development such as providing benefits to the community, reducing the concentration of wealth, realigning the economic/financial sector, making strategic program plans, as well as apply principles tauhid, khilafah, dan ’adalah.